Evidence supporting the use of bone morphogenetic proteins for spinal fusion surgery. (January 2008) - Robinson, Yohan; Heyde, Christoph E; Tschööke, Sven K; Mont, Michael A; Seyler, Thorsten M; Ulrich, Slif D
Bone morphogenetic proteins (BMPs) are capable of promoting bone healing and even induce de novo osteogenesis. Their clinical application in spinal fusion surgery has recently increased in popularity. This is especially true for the use of BMPs in combination with artificial bone substitutes that have the capability to replace autologous bone graft, which can be associated with severe harvesting complications. This review will examine the use of BMP-2 and BMP-7 as commercially available products that have proven their osteoinductive capacity in spinal fusion. We will perform an overview of the literature for scientific evidence supporting the use of these new technologies. Despite their high osteoinductive potency, the use of BMPs does not replace proper surgical stabilization in spinal fusion. Safety issues with BMPs are osteoclast activation, postoperative swelling and hyperostosis. Despite these issues, manufacturers continue to expend more effort concerning proper application, dosage and carriers for these devices for spinal fusion, both presently and in the future.